EKSISTENSI ALTERNATIVE DISPUTE RESOLUTION RESOLUSI DALAM PROSES PENYELESAIAN SENGKETA DI INDONESIA - Leli Joko Suryono (LP3 UMY, 2015)
Some inconveniences are usually faced by people at the time they wenl to the Court to sellle a dispute. The complex process of dispute sefilement especially in trade, environmenl and labor has conlributed to the emergence ofstrong motivationfrom the quarrelling parts lo choose an arbiter other than the official institution. The choice lalls to the system ol Alternative Dispule Resolution, whose erislence and implications in seltling disputes become the object of this research